Responses of New Zealand forest birds to management of introduced mammals. Issue 1 (23rd March 2020) - Fea, Nyree; Linklater, Wayne; Hartley, Stephen
Abstract: Over the past 1000 years New Zealand has lost 40–50% of its bird species, and over half of these extinctions are attributable to predation by introduced mammals. Populations of many extant forest bird species continue to be depredated by mammals, especially rats, possums, and mustelids. The management history of New Zealand's forests over the past 50 years presents a unique opportunity because a varied program of mammalian predator control has created a replicated management experiment. We conducted a meta‐analysis of population‐level responses of forest birds to different levels of mammal control recorded across New Zealand. We collected data from 32 uniquely treated sites and 20 extant bird species representing a total of 247 population responses to 3 intensities of invasive mammal control (zero, low, and high). The treatments varied from eradication of invasive mammals via ground‐based techniques to periodic suppression of mammals via aerially sown toxin. We modeled population‐level responses of birds according to key life history attributes to determine the biological processes that influence species' responses to management. Large endemic species, such as the Kaka ( Nestor meridionalis ) and New Zealand Pigeon ( Hemiphaga novaeseelandiae ), responded positively at the population level to mammal control in 61 of 77 cases for species ≥20 g compared with 31 positive responses from 78 cases for species <20 g. The Fantail ( Rhipidura fuliginosa ) and Grey Warbler ( Gerygone igata ), both shallow endemic species, and 4 nonendemic species (Blackbird [ Turdus merula ], Chaffinch [ Fringilla coelebs ], Dunnock [ Prunella modularis ], and Silvereye [ Zosterops lateralis ]) that arrived in New Zealand in the last 200 years tended to have slight negative or neutral responses to mammal control (59 of 77 cases). Our results suggest that large, deeply endemic forest birds, especially cavity nesters, are most at risk of further decline in the absence of mammal control and, conversely suggest that 6 species apparently tolerate the presence of invasive mammals and may be sensitive to competition from larger endemic birds. Abstract : Article impact statement : Management of introduced mammals across New Zealand has preferentially benefited large and endemic forest birds. Abstract : Respuestas de Aves Habitantes de Bosques Neozelandeses al Manejo de Mamíferos Introducidos Resumen: En los últimos 1000 años, Nueva Zelanda ha perdido entre el 40% y 50% de las especies de aves. De estas extinciones, más de la mitad se puede atribuir a la depredación por mamíferos introducidos. Las poblaciones existentes de aves de bosque todavía están siendo depredadas por mamíferos, principalmente ratas, zarigüeyas y mustélidos. La historia de manejo de los bosques en Nueva Zelanda durante los recientes 50 años representa una oportunidad única porque un programa variado de control de mamíferos depredadores ha creado un experimento de manejo replicado. Realizamos un metaanálisis de las respuestas a nivel poblacional de las aves de bosque ante diferentes niveles de control de mamíferos registrados en toda Nueva Zelanda. Recolectamos datos de 32 sitios tratados de manera única y de 20 especies existentes de aves que representan un total de 247 respuestas poblacionales a tres intensidades de control de mamíferos invasores (cero, bajo y alto). Los tratamientos variaron desde la erradicación de los mamíferos invasores por vía de técnicas terrestres hasta la eliminación periódica de los mamíferos por medio de toxinas dispersadas por vía aérea. Modelamos las respuestas a nivel poblacional de las aves de acuerdo con los atributos de historia de vida importantes para determinar los procesos biológicos que influyen sobre las respuestas de las especies al manejo. Las especies endémicas grandes, como la kaka ( Nestor meridionalis ) y la paloma de Nueva Zelanda ( Hemiphaga novaeseelandiae ), respondieron positivamente a nivel poblacional al control de mamíferos en 61 de los 77 casos para especies con un peso ≥20 g comparado con 31 respuestas positivas de 78 casos para especies con un peso <20 g. El ave cola de abanico ( Rhipidura fuliginosa ) y la curruca gris ( Gerygone igata ), ambas especies endémicas someras, junto con cuatro especies no endémicas (el mirlo [ Turdus merula ], el pinzón [ Fringilla coelebs ], el acentor [ Prunella modularis ] y el pájaro de anteojos [ Zosterops lateralis ]) que arribaron a Nueva Zelanda en los últimos 200 años presentaron una tendencia hacia las respuestas negativas o neutrales al control de mamíferos (59 de 77 casos). Nuestros resultados sugieren que las aves endémicas grandes y que habitan en las profundidades del bosque, especialmente aquellas que anidan en cavidades, tienen el mayor riesgo de vivir una declinación en el futuro si el control de mamíferos se ausenta. A la inversa, nuestros resultados también sugieren que seis especies aparentemente toleran la presencia de mamíferos invasores y podrían ser vulnerables a la competencia generada por aves endémicas de mayor tamaño. 摘要: 不断增长的全球能源需求正在促进可再生能源作为化石燃料的替代能源的发展。然而, 可再生能源设施可能对野生动物产生不利影响。设施选址指南通常建议或要求项目开发者对施工前后的野生动物进行调查, 以预测风险并估计拟建项目的影响。尽管如此, 目前还没有已发表研究对野生动物调查类型的选择和设施内部、设施之间如何确定标准化调查类型做过定量分析。本研究评估了 628 篇同行评审文献、未发表报告及引文, 并分析了其中美国和加拿大的 525 篇文献或报告的数据 (涉及 203 个设施, 包含 193 个风能和 10 个太阳能设施), 以确定施工前后调查的频率及其随时间的变化;明确设计进行施工前后或影响控制分析的研究的频率; 施工前后收集的调查数据类型, 以及这些数据类型在不同时期和不同设施之间的标准化方法。在本研究的数据集中, 设施建设后的野生动物死亡率和栖息地利用的监测是常规标准做法 (446 份报告), 而在建设前对野生动物死亡率及栖息地利用的基线水平的评估较少 (84 份) 。 203 个设施中只有 22% (45 个) 同时提供了施工前和施工后的数据, 有 29% (59 个) 提供了实验研究设计。在进行了栖息地利用调查的 108 个设施中, 只有 3% 包含了动物发现概率的估计。因此, 现有数据普遍不能在不同建设时期和不同设施之间进行生物学数据的比较。我们建议使用实验研究设计并遵循类似的野外研究方法, 以提高对可再生能源影响野生动物的认识。 【翻译: 胡怡思; 审校: 聂永刚】